2022
DOI: 10.1093/plphys/kiac096
|View full text |Cite
|
Sign up to set email alerts
|

ABI5 binding protein2 inhibits ABA responses during germination without ABA-INSENSITIVE5 degradation

Abstract: Overexpression of ABA-INSENSTIVE5 interacting proteins (AFPs) results in extreme ABA resistance of seeds and failure to acquire desiccation tolerance, at least in part through effects on chromatin modification. We tested the hypothesis that AFPs promote germination in Arabidopsis (Arabidopsis thaliana) by also functioning as adapters for E3 ligases that ubiquitinate ABI5, leading to its degradation. Interactions between AFPs and two well-characterized classes of E3 ligases targeting ABI5, DWD HYPERSENSITIVE TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“…The sly1 mutant has a similarly mild increase in storage proteins. In contrast, overexpression of either AFP substantially reduced storage protein accumulation, consistent with recent proteomic studies of the AFP2 overexpression line [ 34 ]; the combination of excess AFP and DELLAs was again intermediate.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The sly1 mutant has a similarly mild increase in storage proteins. In contrast, overexpression of either AFP substantially reduced storage protein accumulation, consistent with recent proteomic studies of the AFP2 overexpression line [ 34 ]; the combination of excess AFP and DELLAs was again intermediate.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, YFP-AFP2 appears to be subject to post-transcriptional regulation resulting in reduced accumulation in the sly1 background. Although the mechanism is not known in this case, the YFP-AFP2 fusion is subject to proteasomal degradation [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genes controlling seed development progress in mungbean are largely unknown ( Ha et al, 2021 ). In this study, we identified fifty-four candidate genes in the seed-development pathways, i.e., aba2 ( Cheng et al, 2014 ; Chauffour et al, 2019 ), ABI5 ( Lynch et al, 2022 ), SHB1 , MINI3, and IKU2 ( Garcia et al, 2003 ; Xiao et al, 2016 ; Zhang H. et al, 2017 ), mutants of those genes induced abnormal seed development in Arabidopsis . And, five genes were also commonly identified via GWAS ( Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, the availability of Arabidopsis tissue-specific proteomic data sets that include seed samples allows one to search for the presence and relative abundance of proteins involved in ABA signalling in a particular physiological context ( Xiang et al., 2016 ; Zhang et al., 2019 ; Bassal et al., 2020 ; Mergner et al., 2020 ; Lynch et al., 2022 ). With 12,392 quantified proteins in the dry seed, data from the Arabidopsis Proteome Atlas currently provide the deepest view on the relative protein abundances in this organ ( Mergner et al., 2020 ; Tena, 2020 ).…”
Section: Resultsmentioning
confidence: 99%